Metastatic nasopharyngeal carcinoma masquerading lymphoma: an unusual presentation - Bhatia, Akanksha; Nath, Devajit; Tiwari, Neema; Sawhney, Megha; Madan, Jyotsna; Bhalla, Deeksha (Journal of Pathology of Nepal, 2025)
Nasopharyngeal carcinoma (NPC) is an Epstein-Barr virus (EBV) associated malignancy of the nasopharynx. Although metastasis to the cervical region is known, however initial presentation with cervical metastasis without apparent mass in the nasopharynx is rare. Herein, we present a case of a 14-year-old male who presented with bilateral multiple cervical lymphadenopathy, clinically mimicking lymphoma; with no mass in nasopharynx even on CT scan. A biopsy of the lymph node revealed a syncytial arrangement of atypical cells with partially compressed lymphoid tissue. On immunohistochemistry, these cells were positive for Pan-cytokeratin and EBV-LMP1 with absent CD45 expression; and a possibility of metastatic deposit arising from nasopharyngeal carcinoma was suggested. MRI revealed a thickening of the posterior nasopharyngeal wall, thereby confirming the origin of the tumor.This case highlights a possible clinical mimicker and the importance of biopsy and immunohistochemistry in reaching a conclusive diagnosis. Clinicians and pathologists must be vigilant and the possibility of NPC must be ruled out even without any obvious mass in the nasopharynx, to avoid delay in further management.